CLINICAL CONDITION AND BLOOD INDICES OF COWS WITH SUBCLINICAL MASTITIS BEFORE AND AFTER APPLICATION OF POLTAVA BISCHOFITE SOLUTION - Berdnyk, V. P.; Rakitina, A. I.; Zavaliy, M. F. (Scientific Progress & Innovations, 2021)
Examination for mastitis by studying anamnesis data, clinical methods, and milk samples in tests with mastidine and sedimentation of 261 farm cows revealed mammary glands inflammation in 57 (21.84 %) an-imals. 5 (1.92 %) cows had clinically expressed forms of mastitis, and 52 animals (19.92 %) had a latent form. In the experiment, 24 cows with latent mastitis and 6 clinically healthy (control) animals were in-volved, being tested with Poltava bischofite solution (PBS) by applying orally and simultaneously by inunc-tion of anti-latent mastitis gel in the skin of the inflamed udder area. The preparation is produced by the “Laboratory of Natural Technologies” LLC in the city of Poltava. During the period of applying the prepa-ration in two cycles, 7 times in each one with a 22–24-hour interval, and with a 7-day interval between the cycles, the cows were clinically healthy. Three cows in each of the groups, which were treated with the prep-arations, showed no signs of latent mastitis on the seventh day of the experiment in the first cycle, and the rest of animals - only on the sixth or seventh day – in the second cycle. In cows treated with PBS in the first cycle, as compared with the control, a reliable increase in the amount of erythrocytes (p<0.05–0.001) and hemoglobin (p<0.05–0.01) was observed, and in the blood serum – magnesium ions (p<0.05) were found. Before the drugs administration and after their use in the first cycle, a significantly increased amount of leu-kocytes was found in the cows’ blood, which reached the normal values only in the second cycle. In all the experimental animals, including the controls, the ratio of "calcium: phosphorus" was impaired due to lack of calcium and excess of phosphorus. It is possible that due to this fact, the part of the cows had to be adminis-tered PBS in the second cycle. Applying preparations based on Poltava bischofite solution at subclinical mastitis of cows has prospects, but requires further testing on farms with different conditions of feeding, care and milk production technologies.